2022
DOI: 10.1212/wnl.0000000000200606
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Treatment With Ponesimod in Relapsing-Remitting Multiple Sclerosis

Abstract: Objective:To evaluate the dose-response relationship of 10, 20 and 40-mg ponesimod and long-term efficacy and safety of ponesimod 20 mg using an analysis of combined data from the phase 2 Core and Extension studies in relapsing-remitting multiple sclerosis (RRMS) patients.Methods:In the Core study, 464 patients were randomized (1:1:1:1): placebo (n=121), 10-mg (n=108), 20-mg (n=116), or 40-mg ponesimod (n=119) once-daily for 24 weeks. Patients who completed the Core study transitioned into the Extension study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Superiority of ponesimod was also shown on the exploratory end points of brain volume loss and NEDA status. Ponesimod was well tolerated, and the safety results were in line with previous observations in its phase 2 dose-finding study and findings on other S1P receptor modulators in controlled studies, including their extensions and postmarketing observations.…”
Section: Discussionmentioning
confidence: 99%
“…Superiority of ponesimod was also shown on the exploratory end points of brain volume loss and NEDA status. Ponesimod was well tolerated, and the safety results were in line with previous observations in its phase 2 dose-finding study and findings on other S1P receptor modulators in controlled studies, including their extensions and postmarketing observations.…”
Section: Discussionmentioning
confidence: 99%
“…During the phase II extension study, the most common adverse events reported were as follows: nasopharyngitis (30%), headache (24%), and upper respiratory tract infection (21%). 15 No serious adverse events with an incidence greater than 1% were reported. Evaluation of clinical efficacy and tolerability of the 40 mg dose of ponesimod after 96 weeks suggested reduced tolerability and no additional efficacy.…”
Section: Safety Studiesmentioning
confidence: 94%
“…After completing the phase IIb core study of 24 weeks, 435 patients were transitioned into an extension study to assess the long-term safety and efficacy of ponesimod. 15 The study was divided into 3 treatment periods: TP1, TP2, and TP3 (Table 2). The primary efficacy endpoints of the study were time to first confirmed relapse, the mean ARR, and time to 6-month confirmed disability accumulation (CDA).…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Patients who participated in the phase II study rolled over into its extension, in which they were all treated with ponesimod 20 mg. After a median exposure of more than 8 years, between core and extension studies, the drug confirmed its substantial safety. No SAEs with an incidence greater than 1% were reported and the most common adverse events were nasopharyngitis (30%), headache (24%) and upper respiratory tract infection (21%) (33).…”
Section: Safetymentioning
confidence: 99%
“…Patients who had completed the core study were offered enrollment in the extension of the phase II trial (NCT01093326), in which all 353 participants were treated with ponesimod (33). In an early part of the study, patients were still given the three different doses of ponesimod.…”
Section: Clinical Studiesmentioning
confidence: 99%